HIGH CARDIOVASCULAR RISK IN PATIENTS WITH PSORIASIS - DR MEGHA KATARIA ARORA MD; DR SHASHI SETH MD; MAMTA SETH (International Journal of Pharma and Bio Sciences, 2011)
Dyslipidemia is one of the important risk factor for cardiovascular disease so present study was planned to evaluate risk of cardiovascular disease in patients with psoriasis. It was a hospital based case control study performed in the 85 patients of psoriasis with <25% body surface area involved. The study was done in a tertiary care setup. The patients attending the Dermatology OPD were enrolled for study. Lipid profile was evaluated to determine the cardiovascular risk in patients as compared to 85 age- and sex- matched controls. Total cholesterol (TC), LDL-C, VLDL-C, triglyceride and apolipoprotein B levels were higher in patients as compared to controls. HDL-C and apolipoprotein A1 levels were low in patients and the difference was statistically significant. Abnormality of lipid profile must be taken into account in patients of psoriasis and they must be advised lifestyle modifications to decrease the risk of cardiovascular disease